IMPLEMENTATION FINTECH ON THE NUMBER AND SATISFACTION OF BMT UGT NUSANTARA MEMBERS - Aisyah, Siti; Hidayatullah, Indra; Farid, Muhammad; Alfarisi, Salman (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Financial Technology (Fintech) is an innovation in the financial sector that utilizes modern technology to simplify services, such as payments, investments, transfers, and financing. This study aims to describe the implementation of fintech in increasing the number and satisfaction of members of BMT UGT Nusantara Pasirian Branch, and analyze its impact on the institution's performance. The study used a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, then analyzed by comparing theory and practice in the field. The results show that the implementation of the Mobile UGT application has made a significant contribution to simplifying transactions, increasing trust, and expanding the reach of services. The positive impacts felt are an increase in the number of members, better service quality, and increased member satisfaction